2015
DOI: 10.1007/s11814-015-0115-x
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical degradation of the Acid Orange 10 dye on a Ti/PbO2 anode assessed by response surface methodology

Abstract: The decolorization and degradation of the synthetic aqueous solution of the Acid Orange 10 (AO10) dye on Ti/PbO 2 anode were investigated using the response surface methodology based on central composite design with three variables: current density, pH, and supporting electrolyte concentration. The Ti/PbO 2 electrode was prepared by the electrochemical deposition method. The optimum conditions for AO10 decolorization in synthetic dye solution were electrolyte concentration of 117.04 mM, pH of 12.05, and curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Then, the Ti, as anode, and the stainless steel, as cathode, were placed in electrochemical solutions containing 12% lead nitrate, 5% triton X‐100 and 3% copper (II) sulfate pentahydrate. Finally, electrodeposition of PbO 2 on Ti was performed at current density 20 mA cm −2 , electrolysis time 60 min and temperature 80 °C …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Then, the Ti, as anode, and the stainless steel, as cathode, were placed in electrochemical solutions containing 12% lead nitrate, 5% triton X‐100 and 3% copper (II) sulfate pentahydrate. Finally, electrodeposition of PbO 2 on Ti was performed at current density 20 mA cm −2 , electrolysis time 60 min and temperature 80 °C …”
Section: Methodsmentioning
confidence: 99%
“…38 However, when the current density increased to 25 mA cm −2 , AO10 removal efficiency decreased. This may be due to the formation of a parasitic electrochemical reaction such as reducing oxygen to water instead of H 2 O 2 on graphite [Eqn (6)] and oxidizing the water to oxygen instead of •OH on Ti/PbO 2 [Eqn (7)]. 39 electro-Fenton process combined with Kaolin/Fe-Cu.…”
Section: Effect Of Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such morphology suggested that the Ti substrate was completely coated by PbO 2 . Therefore, the RhB was degraded only by PbO 2 [31,39]. Compared with PbO 2 -Ti, there were more defects and cracks on the surface of SnO 2 /Sb-Ti (see Figure 1d).…”
Section: Sem Of Pbo 2 -Ti and Sno 2 /Sb-timentioning
confidence: 99%